Decarbonizing Infrastructure in Indonesia: Opportunities, Barriers, and Stakeholder Perspectives - Hidayat, Lenny; Ramadhan, M. Ilham; Tasliman, Michael Timothy; Octora, Anggita (PT Penjaminan Infrastruktur Indonesia (Persero), 2025)
Infrastructure development is a major driver of climate change, accounting for 79% of global greenhouse gas (GHG) emissions and 88% of adaptation costs since 2022. In Indonesia, emissions are led by the energy sector (31%), which remains coal-dependent for power infrastructure operations. Other contributors include transport (17%), wastewater (8%), solid waste (5%), and process emissions from cement (5%) and iron–steel (6%). While the country has rapidly expanded roads, ports, airports, and dams, these gains have coincided with deforestation and reduced carbon sequestration. This study investigates barriers and stakeholder aspirations for decarbonizing Indonesia’s infrastructure by applying a 5M business management lens—material and machine, methodology, money, and manpower—aligned with four decarbonization pillars (reduce, reuse, replace, remove), using evidence from focus group discussions, desktop reviews, and inductive analysis. Findings identify four principal barriers: (i) materials and technology—uptake of low-carbon options is constrained by cost perceptions and limited use of recycled inputs; (ii) standards and regulation—fragmented guidance and weak enforcement of green procurement; (iii) cost and funding—high certification expenses and underdeveloped green finance instruments; and (iv) skills and capabilities—insufficient technical expertise in low-carbon practices. Stakeholders call for systematic material mapping, stronger tax incentives, adoption of harmonized standards, and deeper academia–industry collaboration. The study proposes a policy roadmap to coordinate actors and accelerate infrastructure decarbonization.